Opinions and beliefs in vaccine hesitant parents in Italy: what makes the difference. (13th November 2019) - Cocchio, S; Bertoncello, C; Fonzo, M; Zanovello, S; Bennici, S E; Baldovin, T; Buja, A; Napoletano, G; Russo, F; Baldo, V
Abstract: : Vaccine hesitancy has been defined as the delay of acceptance or refusal of vaccines. Hesitant parents' (HP) fluctuate between anti-vaccine (AP) and pro-vaccine parents' (PP) positions. In the light of alarming results from recent Eurobarometer 488, our aim was to identify sensitive topics harbouring the widest opinion gap between HP and PP. In 2017, an online questionnaire was administered to parents with children aged 3-84 months. Parents were classified as PP, HP or AP based on self-reported vaccine status and timeliness of vaccinations. Agreement with 25 items was assessed with 5-point Likert scale. Items were combined into 8 topics (benefit/risk of vaccines, trust/mistrust in healthcare workers, administration policies, complacency, sense of community, freedom of choice) and scores calculated. Internal consistency was evaluated with Cronbach's α; t-tests (sig. <.05) were used (Norman G, 2018). The study included 3, 865 parents (64% PP; 32% HP; 4% AP). Cronbach's α ranged 0.77-0.92. The widest gap concerned the sense of community: HP (2.7/5.0) cared significantly less than PP (4.7) about the usefulness of vaccine in protecting other children and claimed for a complete freedom in decision to vaccinate (3.6) more than PP (1.8). HP were worried (4.1) about current vaccination schedule (PP 2.1): simultaneous administration and age at vaccination (considered too young) were matter of concern. Among HP, mistrust of healthcare workers (3.7) and fear of side effects (3.8) played an important role, but the gap with PP was narrower compared with abovementioned topics; awareness in vaccine benefits reached 3.7. Agreement with complacent attitudes was low (2.2) with the least difference with PP (1.2). HP showed to partially consider benefits of vaccines on a community scale, claiming for a private nature of this choice. The existence of a consistent opinion gap about the vaccination schedule may suggest the need for a sharper focus on current communication tools and strategies. Key messages: While hesitant parents share some concerns with pro-vaccine, relevant opinion gaps may serve as warning lights, pointing at topics potentially harbouring the most sensitive drivers of hesitancy. Communication strategies should primarily focus on raising acquaintance of hesitant parents with benefits arising from herd immunity and compliance with the suggested vaccination schedule.